Aliansi Politik Kebangsaan Menurut Al-Qur’an Dan Sang Maha Guru - Hartono, Hartono; Nurhalim, Nurhalim (LPPM Sekolah Tinggi Ilmu Al-Qur'an Wali Songo Situbondo, 2019)
During this time, many politicians were political without using the Qur'an's values to fight. Quite often from them they commit political rape which is very tarnishing the essence of politics. In fact, they were born from Rahim political party political parties. By Karen, it is time for Islamic politicians to re-understand, interpret and implement the Qur'an-based politics, based on the Sunnah of the Prophet and based on the sunnah of friends and follow ulamak whose knowledge is connected to the prophet and his heart contains Allah, the mind of the Ummah.